Determination of Tetracycline Using Ultrasound-Assisted Dispersive Liquid–Liquid Microextraction Based on Solidification of Floating Organic Droplet Followed by HPLC–UV System. (26th March 2021) - Rahimi Moghadam, Mojtaba; Zargar, Behrooz; Rastegarzadeh, Saadat
Abstract: Background: Tetracyclines (TCs) are a group of broad-spectrum antibiotics that may be used to control bacterial diseases in humans or are applied as feed additives to enhance growth in farm animals. TCs are released into the aquatic environment via different pathways. Many analytical methods combined with a preconcentration step have been introduced for the determination of TC in various environmental samples. Objective: The objective this paper is developing reliable analytical methods for determination of TC trace in various environmental samples. Method: In the present work, combined ultrasound-assisted and dispersive liquid–liquid microextraction according to the solidification of floating organic drop as a sample preconcentration procedure for determining TC hydrochloride HPLC in water and serum samples was used. Results: A series of parameters, including the type and volume of disperser and extraction solvents, salt effect, extraction time, and pH of solution influencing the extraction efficiency of UA-DLLME-SFO was examined. Enrichment factors were in the range of 125–137 for TC hydrochloride under optimum conditions. The linear range was calculated from 0.005 to 3 mg/L and LOD at 0.002 mg/L. RSDs were in the range of 2.7 to 3.2 ( n = 5). The UA-DLLME-SFO method used in water and serum samples revealed good extraction recoveries with RSD of 2.7–4.3%. Conclusions: This method significantly decreased the organic solvent volume from 3 mL to 90 µL, also LOD and linear ranges were lower than or almost close to levels obtained in other research studies. In this procedure, an ultrasound bath enhanced the mixing and contact between the sample solution and the extraction solvent.